PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER KREATIF DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA SUB POKOK BAHASAN KESEBANGUNAN - Setya Putri, Inge Wiliandani; Sunardi, S; Kurniati, Dian (KadikmA, 2014)
Abstract. The research aims to know process and result of developing of mathematics learning aids based on creativity with realistic mathematics education approach for similarity sub topic at ninth grade junior high school. The research development modle refers to 4D Thiagarajan models. The subject of research is students of IX-A class SMPN 11 Jember in even semester academic year 2013-2014. The data of research are obtained by validation sheet, observation sheet of teacher and students activities, and observation sheet of character.The product of this research are lesson plan, studenthandbook, and worksheet.The validity of those product consecutively are 4; 4,5; 4,05. The average percentage of teacher activity is 82% and 90%, student activity is 82% and 80%.The result shows that the learning instruments qualifies validity, practical, but not effective criteria. The reason is not effective because creative character of the students only 41% and 31%. Keywords:Realistic Mathematics Education,Creative Character, Learning